Implementasi Literasi Media Digital APLT untuk Mendukung Pendidikan Seksual pada Anak Usia Dini - Dina Amalia; Dewi Pratiwi; Fatimatuzzahroh Fatimatuzzahroh (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
Sex education in early childhood is a preventive effort to foster children’s understanding of body protection and privacy awareness. This study aimed to develop and examine the feasibility and effectiveness of APLT (Aku Pintar Lindungi Tubuh) digital media as a supporting tool for early childhood sex education. The study employed a Research and Development (R&D) approach using the ADDIE model (analysis, design, development, implementation, and evaluation). The effectiveness of the developed media was tested using a pre-experimental one group pretest posttest design. The results indicate that the APLT media was highly feasible, based on expert validation. Effectiveness analysis using normalized gain (N-gain) showed a moderate level of effectiveness, indicating an improvement in children’s understanding of body protection concepts, including protected body parts, appropriate and inappropriate touch, and body privacy awareness. These findings suggest that APLT media is moderately effective and functions as a supportive learning resource rather than a stand alone intervention. Therefore, APLT digital media has the potential to support early childhood sex education within a limited and guided instructional context, particularly in strengthening children’s initial understanding of body protection and privacy awareness.